The efficacy of delayed, repeated reduction enema in management of intussusception - Tamer Fakhry; Ahmed Nabil Fawzy; Ahmed Taher Mahdy (SpringerOpen, 2021)
Abstract Background Management of intussusception varies according to the case, time of presentation, cause, and symptoms. In this study, we focus on describing the demographic and sonographic characteristics of children with intussusception with failed initial enema reduction who were managed by delayed repeated enema attempts and identify predictors associated with successful repeated reduction. Results This study was conducted in the period from December 2018 to April 2020 at university hospitals (pediatric surgery unit). This study included 40 patients with intussusceptions; 27 are males, and 13 of them are females. Their ages ranged from 5 months to 3 years old. Patients in this study had failed initial enema reduction attempts under sonographic guidance and had subsequent delayed (≥ 2 h from the initial attempt) repeated enemas made up the study population. Of the 40 patients, 34 patients (85%) were successfully reduced, and 6 patients (15%) failed reduction and required surgical intervention. There were no deaths, perforation, or resection of gangrenous bowel. Two cases showed recurrences, but required no surgical intervention. It is also noted that early presentation (< 12 h), stable, non-complicated, and with little or no bloody diarrhea are predictors of successful DRE. Conclusion Delayed repeated enema in the treatment of intussusception is a viable option in patients with unsuccessful initial enema reduction provided that early presentation, stable vitals, and no signs of perforation or peritonitis are present.